Sobre a ocorrência de ondas extremas (Rogue waves) no litoral do Ceará com base nos dados do ondógrafo do Pecém. - Gonçalves, Alysson Daniel Ribeiro (2017)
The oceans have several types of waves, among these types there are those that are caused by the action of the wind, at the air-sea interface, and that will be approached in this study. The waves can cause accidents with boats in the sea or even to buildings near the coast. The coast of Ceará suffers from this type of accident, near the coast of Ceará. It is suspected that the accidents with the rafts and the problem of destruction of the buildings near the coast, as those occurred in the beach of Icaraí are related to the extreme waves. The study area was chosen based on the availability of wave measurements, unprecedented in the region, made by a directional waveguide installed near the coast, from the study of data from observations from 1997 to 2001. In order to investigate the possible cause of these accidents, the objective of this study is to investigate the occurrence of extreme waves in the coast of Ceará and possible impacts and consequences.